2023
DOI: 10.1136/jitc-2023-006764
|View full text |Cite
|
Sign up to set email alerts
|

Use of cytokine-induced killer cell therapy in patients with colorectal cancer: a systematic review and meta-analysis

Abstract: BackgroundThe number of clinical studies evaluating the benefit of cytokine-induced killer cell (CIK) therapy, an adoptive immunotherapy, for colorectal cancer (CRC) is increasing. In many of these trials, CIK therapy was coadministered with conventional cancer therapy. The aim of this review is to systematically assess the available literature, in which the majority were only in Chinese, on CIK therapy for the management of CRC using meta-analysis and to identify parameters associated with successful CIK ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…We recently reported that past clinical studies on CIK cell therapy for CRC were generated from autologous patient-derived PBMCs [11]. Thus, we investigated if PBMCs from CRLM donors have similar capacity to produce CIK cells as healthy donors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that past clinical studies on CIK cell therapy for CRC were generated from autologous patient-derived PBMCs [11]. Thus, we investigated if PBMCs from CRLM donors have similar capacity to produce CIK cells as healthy donors.…”
Section: Resultsmentioning
confidence: 99%
“…Media usage ranged from SFMs to serum supplemented media including the use of human serum and FBS ([11] and unpublished observations). While FBS supplementation is still common practice in cell culture for T cell therapies [39], its use increases the risk of xenoimmunisation and zoonotic disease transfer in recipients [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Among them, CIK/DC-CIK cells have shown promising outcomes in initial clinical trials and demonstrated synergistic anti-tumor effects when coadministered with conventional cancer therapy. 13 , 15 …”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 A recent meta-analysis involving 6743 patients from 70 studies also supports this finding, showing that adoptive CIK/DC-CIK cell immunotherapy in combination with standard treatment protocols, particularly chemotherapy, offers remarkable clinical benefits for patients with CRC. 13 However, there remains a lack of randomized, controlled, multicenter clinical studies to further confirm the therapeutic efficacy of adoptive immune cell therapy in CRC.…”
Section: Introductionmentioning
confidence: 99%